2023
DOI: 10.1007/s12571-023-01407-y
|View full text |Cite
|
Sign up to set email alerts
|

Food system resilience measurement: principles, framework and caveats

Christophe Béné,
Timothy R. Frankenberger,
Suzanne Nelson
et al.

Abstract: There is growing recognition that a better understanding of how food systems respond to crises is critical to build and protect the food security of local populations. But rigorous and reliable methods to measure food system resilience are still missing. In this paper, we build on the current literature to develop an analytical framework aimed at assessing the resilience of food systems at local level. The novel element of the analysis lies in the levels at which resilience is considered. Combining the individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Research should delve into identifying which indicators prove most descriptive and useful across different levels and components of the food system and identify the minimum set of indicators that can be used to measure the entire food systems continuum ( 13 , 48 ). These should be relevant for and applicable to diverse food systems at both national and subnational levels.…”
Section: Discussionmentioning
confidence: 99%
“…Research should delve into identifying which indicators prove most descriptive and useful across different levels and components of the food system and identify the minimum set of indicators that can be used to measure the entire food systems continuum ( 13 , 48 ). These should be relevant for and applicable to diverse food systems at both national and subnational levels.…”
Section: Discussionmentioning
confidence: 99%
“…We used a food system approach to better understand the effect of mobility restrictions on household food security. Figure 1 describes the different stepwise activities of the food system (i.e., production, processing, sale, and consumption) and the various actors involved in each step, as defined by the UN Food and Agriculture Organization's (FAO) High Level Panel of Experts on Food Security and Nutrition of the Committee on World Food Security (CFS) (Ericksen, 2008;HLPE, 2014HLPE, , 2017Béné et al, 2016Béné et al, , 2023. The food system outcomes contributing to food security dimensions such as food access and availability (Ericksen, 2008;Ingram, 2011), and are affected by shocks and stressors (socioeconomic drivers), such as changes in demography or income.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In terms of grain resilience measurement, most scholars increasingly recognize that grain industry resilience is a critical path to address the grain security crisis, but there is still a lack of accurate methods to measure grain system resilience. Béné et al reported that grain system resilience is derived from individual actors and phylogenetic processes, and established a system for assessing grain resilience consisting of absorptive capacity, adaptability and reform capability [15]. Specifically, tangible elements include easily measurable capabilities such as improved farming methods, income levels, livelihood diversification, and safety nets.…”
Section: Literature Reviewmentioning
confidence: 99%